Idiopathic Pericarditis Leading to Hemorrhagic Pericardial Effusion- A Case Report and Review - BS , Forest Riekhof; Hoque, Farzana (Journal of Medicine, 2024)
Pericardial effusion presentation is a large spectrum that can vary from asymptomatic to cardiac tamponade. It is a relatively common syndrome and has a diverse set of etiologies including infections, malignancy, radiation/iatrogenic, pericardial injury, metabolic disturbances, endocrine disease, connective tissue disease, autoimmune disorders, trauma, or idiopathic. Pericardial drainage is recommended in most large pericardial effusions or those causing cardiac tamponade. Pericardial fluid can be either purulent, serous, serosanguinous, or hemorrhagic. In the case of hemorrhagic effusion, the common etiologies include malignancy, iatrogenic, and tuberculosis (in endemic regions). Large hemorrhagic pericardial effusions resulting from idiopathic (presumed viral) pericarditis are rare but possible. We present an interesting case of a woman with a large hemorrhagic pericardial effusion presenting as subacute cardiac tamponade caused by idiopathic pericarditis in the setting of known malignancy. This report aims to increase awareness about pericarditis as a potential cause of significant hemorrhagic pericardial effusions, rather than solely attributing them to malignancy. J MEDICINE 2024; 25: 87-89